2013
DOI: 10.4103/2230-8210.113769
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between anthropometry and lipid profile in type 2 diabetics

Abstract: Over a period of time, anthropometric parameters have evolved into reliable indicators for predicting the incidence of diabetes mellitus. A number of studies have shown correlations between anthropometry and lipid profiles in healthy volunteers. This study examined correlations between anthropometry and lipid profile in type 2 diabetics. The limited observations made in this study reveal that anthropometric parameters are not ideal for predicting lipid profile abnormalities in type 2 diabetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 8 publications
1
16
1
1
Order By: Relevance
“…Similar studies have been conducted by other authors [5][6][7][8][9][10]. Y. Himabindu et al reported statistically significant positive correlation between BMI (≥25 kg/m 2 ) and VLDL (PC=0.273, P=0.033), and significant inverse correlation between WHR and HDL in T2DM patients without hypertension (PC= -0.261, P=0.048) [2]. SW Masram et al found a positive correlation between the total cholesterol and HbA1c (PC=0.586 p <0,001), and inverse correlation between HbA1c and HDL-cholesterol (PC = -0.22) [3].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Similar studies have been conducted by other authors [5][6][7][8][9][10]. Y. Himabindu et al reported statistically significant positive correlation between BMI (≥25 kg/m 2 ) and VLDL (PC=0.273, P=0.033), and significant inverse correlation between WHR and HDL in T2DM patients without hypertension (PC= -0.261, P=0.048) [2]. SW Masram et al found a positive correlation between the total cholesterol and HbA1c (PC=0.586 p <0,001), and inverse correlation between HbA1c and HDL-cholesterol (PC = -0.22) [3].…”
Section: Resultssupporting
confidence: 84%
“…Conducted surveys focused exclusively on clarifying the etiology, pathogenesis, clinical course and treatment of the disease. Limited number of studies aimed at clarifying the relationship between anthropological parameters governing humans' body constitution, and the lipid profile and glycated hemoglobin values of T2DM patients [2,3,4]. Many similar studies have been conducted in India [2-8, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…The study by [29] also showed that Cholesterol levels in turn correlate with BMI indicating that lipid levels are influenced by BMI. A study showed that positive correlations were seen only between BMI > 25 kg/m 2 and VLDL in the total study group [30]. Plasma lipids were positively correlated with BMI and artherogenic indices, except for HDL-C, which was negatively correlated to artherogenic indices and LDL-C but was positively correlated with BMI in another study [31].…”
Section: Discussionmentioning
confidence: 93%
“…Y Himabindu et al (2013) in their research found that positive correlations were seen only between BMI > 25kg/m 2 and VLDL in the total study group. [9] Plasma lipids were positively correlated with BMI and atherogenic indices, except for HDL-C, which was negatively correlated to atherogenic indices and LDL-C but was positively correlated with BMI in another study by EI Ugwuja et al (2013).…”
Section: Discussionmentioning
confidence: 86%